2021
DOI: 10.28991/cej-2021-03091662
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Flexural and Shear Strength of RC Beam Reinforced by Glass Fiber-Reinforced Polyurea (GFRPU)

Abstract: The Glass Fiber-Reinforced Polyurea (GFRPU) which is the composite by the elastic polyurea and milled glass fiber have the mechanical characteristics to enhance tensile strength as well as ductility. It must be reinforcement materials in repair and retrofit applications for strengthening structural capacity and has a merit of simple construction of spray coating to prevent the debonding from concrete surfaces unlike the existing strengthening methods such as Fiber-reinforced polymer (FRP) or steel plate. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Greene & Myers (2013) and L. Zhang et al (2022) discovered that polyurea coatings considerably enhanced the concrete's cracking resistance, boosting its overall performance [ 18 , 45 ]. The application of SEM has provided a potent analytical tool for evaluating the influence of polyurea coatings on various properties of concrete, such as corrosion resistance, fatigue behavior, freeze-thaw resistance, fire resistance, fracture toughness, and adhesion to other coatings [ 11 , 46 ]. This literature study demonstrates that the application of polyurea coatings can greatly enhance the quality and service life of concrete structures [ 47 , 48 ].…”
Section: Success Identificationmentioning
confidence: 99%
“…Greene & Myers (2013) and L. Zhang et al (2022) discovered that polyurea coatings considerably enhanced the concrete's cracking resistance, boosting its overall performance [ 18 , 45 ]. The application of SEM has provided a potent analytical tool for evaluating the influence of polyurea coatings on various properties of concrete, such as corrosion resistance, fatigue behavior, freeze-thaw resistance, fire resistance, fracture toughness, and adhesion to other coatings [ 11 , 46 ]. This literature study demonstrates that the application of polyurea coatings can greatly enhance the quality and service life of concrete structures [ 47 , 48 ].…”
Section: Success Identificationmentioning
confidence: 99%
“…Wu et al [19] investigated the reinforcing effect based on the coating thickness and compared the reinforcement effect for nonreinforced and polyurea-reinforced clay brick walls against blast loads. The reinforcement effect on concrete beams and columns reinforced by glass fiber-reinforced polyurea (GFRPU) mixed with milled glass fiber to improve the tensile strength of polyurea [20][21][22][23] was investigated. The authors reported that GFRPU was effective in enhancing the strength and ductility of structural members.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the tests indicated that the proposed jackets could increase the energy absorption capacity by about four times. Song and Eun [10] investigated the beams retrofitted with glass fiberreinforced polyuria. The proposed method increased flexural ductility about 8.52 to 13.9 times.…”
Section: Introductionmentioning
confidence: 99%